Resilience, conflict and areas of limited statehood in Iraq, Lebanon and Syria. Issue 7 (3rd October 2021) - Huber, Daniela; Woertz, Eckart
ABSTRACT: In a context of areas of limited statehood and contested order, Iraq, Lebanon and Syria have been affected by similar diffuse global and more specific regional and local risks over the past two decades. Yet they differ in outcomes. Lebanon has not descended into civil war despite fears that the one raging in Syria might spill over to its territory and Iraq has coped better over the past decade than Syria has – despite having been subject to various forms of conflict since 1980. We analyse this variance by asking to what extent resilience might buffer against violent conflict and governance breakdown. Through a comparative discussion of sources of resilience – social trust, legitimacy and institutional design – we find that limited input and threatened output legitimacy are harmful to resilience, while collective memory and reconciliation, as well as flexibility of institutions are crucial factors of resilience. Nonetheless, our findings caution that resilience should not only mean the capability to adapt to crises but also needs to set the stage for comprehensive and inclusive transformations that are locally rooted.